Sistem Pembayaran Keuangan Negara Digital dan Kinerja Pegawai di Masa Pandemi Covid-19 - Muhammad Heru Akhmadi; Salsabiyla Aden (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2023)
The Social Restrictions Policy in Pandemic Covid-19 has affected the performance of employees in government agencies. This study aims to analyze the factors that influenced the performance of KPPN employees during the Covid-19 pandemic. The study uses the Structural Equation Model (SEM) to examine the effect of three exogenous variables: eSPM digital services, workload, and transformational leadership on the performance of KPPN employees. The data collected came from a sample of 205 respondents who were randomly selected to represent the population of KPPN employees in the working areas of the provinces of East Java and Central Kalimantan. The results showed that e-SPM digital services, workload, and transformational leadership had a significant positive effect on the performance of KPPN employees during the Covid-19 pandemic, each of 0.374; 0.136 and 0.442. The results of this study prove that e-SPM digital service innovation can maintain the performance of KPPN employees during the Covid-19 pandemic. Transformational leadership at the Directorate General of Treasury has supported the performance improvement of KPPN employees. The recommendation for further research is to improve the exogenous variable instrument to get the perfection of the employee performance measurement model.